Manifest Technique : Hip Hop, Empire, and Visionary Filipino American Culture - Villegas, Mark R. (Book collections on Project MUSE., 2021)
"Filipino Americans have been innovators and collaborators in hip hop since the culture's early days. But despite the success of artists like Apl.de.Ap of the Black Eyed Peas and superstar producer Chad Hugo, the genre's significance in Filipino American communities is often overlooked. Mark R. Villegas considers sprawling coast-to-coast hip hop networks to reveal how Filipino Americans have used music, dance, and visual art to create their worlds. Filipino Americans have been exploring their racial position in the world in embracing hip hop's connections to memories of colonial and racial violence. Villegas scrutinizes practitioners' language of defiance, placing the cultural grammar of hip hop within a larger legacy of decolonization. An important investigation of hip hop as a movement of racial consciousness, Manifest Technique shows how the genre has inspired Filipino Americans to envision and enact new ideas of their bodies, their history, and their dignity"--